A SUSTAINABLE PATHWAY FOR CARBON NEUTRAL ENERGY PRODUCTION - Jan Sher Khan; Khalid Rehman; Ali Mujtaba Durrani; Zaheer Farooq; Hashim Ali (Spectrum of Engineering Sciences, 2025)
The increasing global energy demand, coupled with the urgent need to mitigate environmental degradation, necessitates such innovative solutions that can address both challenges. This research presents a sustainable approach to converting carbon dioxide (CO₂), a predominant greenhouse gas, into a valuable energy resource. By implementing the Sabatier reaction, in which CO₂ is hydrogenated using renewable hydrogen produced via water electrolysis, resulting in the synthesis of methane (CH₄). The methane generated is a fuel which has the ability of producing electricity. From which we gain an effective transformation of a harmful emission such as CO₂ into a clean energy source. This entire process is modeled and simulated by using Simulink/MATLAB that is integrating all necessary chemical reactions by optimizing it through a Model Predictive Controller (MPC) which will be able to ensure efficient energy conversion and maintain system stability. This process includes CO₂ capture, hydrogen production, and methane synthesis, with a dynamic controller (MPC) to maximize its performance. The results shows a fluent methane output of 0.98 mol/s, a power generation efficiency of 39.8%, and a 35% reduction in CO₂ emissions compared to traditional combustion processes. The total efficiency of system reaches to a high value of 57.1%, which shows that how potential this method is to reduce the energy crisis while mitigating the adverse effects of CO₂ on our environment. This combined approach do not address the important issue of CO₂ emissions but it also contributes to energy sources that we are already using which enhances energy production, by transforming CO₂ into a resource for electricity generation. This study offers a viable pathway toward achieving net-zero emissions while supports the global transformation to sustainable energy systems.